Developing a Literature-Based Instructional Material for Essay Writing Course - Lestari Setyowati; Sony Sukmawan; Ana Ahsana El-Sulukkiyah (Universitas PGRI Madiun, 2020)
The inclusion of literature for language teaching is not something new. Nowadays, the use of literature is becoming quite common for teaching language skills. The purpose of this study is to develop an instructional material by using literature-based instruction for essay writing course in University of PGRI Wiranegara, Pasuruan. The research used Gall, Borg, & Gall research and development procedure with some adaptations. The instruments used in the study were questionaires, interview, and tests. The instructional material was tried out and tested to students who joined essay writing class in the academic year 2018-2019. The students’ essays were analyzed by using Jacobs ESL Composition profile covering five elements, namely content, organization, vocabulary, language and mechanics. The result of the study shows that the instructional material was proven to be adequately successful to be used for essay wrting course. The use of literature for teaching writing gives benefits for the students, not only in terms of their writing skills, but also sharpen their critical thinking ability.